Analisis Pengetahuan dan Sikap Sanitasi Wisatawan Kawasan Ekonomi Khusus (KEK) Mandalika - Lalu Muhammad Aby Dujana; Hilman Ahyadi; Ernawati Ernawati; Isrowati Isrowati; Rachmawati Noviana Rahayu (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
This study aims to analyze the level of sanitation knowledge and attitudes among tourists in the Mandalika Special Economic Zone (SEZ). This research employs a quantitative approach with a descriptive design. Data were obtained through structured questionnaires distributed to 98 respondents selected using the Slovin formula. The variables examined include sanitation knowledge and attitudes with four main indicators, namely the use of clean water, utilization of trash bins, toilet usage, and liquid waste management. The research instruments underwent validity and reliability tests to ensure data suitability. The research results indicate that tourists' sanitation knowledge is in the good category at 55%, while sanitation attitudes are in the good category at 58%. Based on the research results, it can be concluded that there is a significant relationship between the level of knowledge and sanitation attitudes among tourists in the Mandalika SEZ. Overall, the research results show that tourists in the Mandalika SEZ have fairly good sanitation knowledge and attitudes, but improvements are still needed in several aspects to support the creation of clean, healthy, and sustainable tourism.